A Case Study of Knowledge Exchange in a Hierarchical Mechanism - Indria Handoko (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
This research investigates knowledge exchange in an organization applying hierarchical mechanisms, and the influence of social interactions on knowledge flow across different levels of analysis. The research uses a qualitative case study method of an Indonesian automotive component-making company, applying semi-structured interviews, observations, and focus groups at interorganizational, internal company, and shop floor levels. The research main finding is that in an organization applying hierarchical mechanisms, social interactions that exist at one level are able to influence interactions at other levels, and that the interactions can both facilitate and inhibit knowledge exchange across levels and boundaries. The application of any formal mechanism at interorganizational level needs to consider both the dynamics operating at social level and the potentially disparate and contradictory effects it may have if its aim is to promote knowledge flow across levels. The application of in-depth exploratory case study research contributes to the conceptualization of relationships between knowledge exchange, social interactions, and governance mechanism.